Impact of COVID-19 on social, Economic & Political: Challenge and Solutions - Gupta, Rajeev Kumar (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
COVID-19, in the first four decades of the corona virus, is known for major changes in the economy, social and political spheres. Making significant changes in the lives of people around the world. The actual potential of the technology developed only after the arrival of the corona virus. Fever, cough and phlegm, fatigue, shortness of breath, body and headache, chills etc. It is considered a symptom of corona. Due to this, lock-in has been done all over the world. Since the lockdown of almost 2 months in the country, the number of positive cases of COVID-19 has increased significantly. Give thanks and thanks to doctors, nurses, policemen, and manual scavengers. Our social and political activists involved in these difficult situations have also done a different job. Reckless and helpless people whose economic condition is not good, they have to work for ration distribution, but the world economy is thinking about the impact on the world economy. The government announced a lockout to prevent the spread of corona virus infection. If the figures are to be believed, the covid-19 from the Asia-Pacific region could suffer a loss of $ 620 billion. It has been observed that many times the disease takes chaotic form due to ignoring the common cough and cold and getting out of control. For this reason people keep cleaning their hands and take care of their health. And finally, our advice is not to worry, be happy, make yourself aware of yourself and the people around you. Our doctors, our governments and economist officials are engaged in dealing with this epidemic day and night. Keywords: COVID-19, Coronavirus, Social, Economy, Political, Challenges, Solutions